An overview of the study of the right habitat and suitable environmental factors that influence the success of edible bird nest production in Malaysia - Azahar, Idris; Abdul Aziz, Abdullah; Munirah, Abd-Rehman (2014)
The estimated value of the world Edible Bird Nest (EBN) production business is worth more than a staggering MYR 10 billion. Despite the huge demand for EBN, the present supply is still less than 50% of the global demand. Numerous factors are responsible for the success of this industry. Habitat and environmental factors have significant impact on the productivity EBN production. The objective of this study is to identify the right habitat and suitable environmental factors that influence successful EBN production. The study will be conducted in two phases. The inital part of the first phase is to identify the habitat and environmental factors extracted through review of literature and supporting documents from the stakeholders of the EBN industry. The last part of the first phase of the study is by interviewing the stakeholders of the industry. The stakeholders of the swiftlet industry are EBN producers, consultants of swiftlet houses, associations of the EBN producers, the key personnel from the Federal and State Department of Veterinary Services and the Local Government Authorities. For the second phase of the study, experimental works will be conducted in 15 swiftlet houses. Several environmental factors such as air and surface temperatures, Relative Humidity (RH), air velocity and light intensity will be observed in the swiftlet houses. The expected findings will reveal the right habitat and the list of suitable and conducive environmental factors that lead to productive EBN production. It is envisaged that these findings would provide an invaluable insight for stakeholders of the industry regarding the most appropriate habitat and suitable environment for successful EBN production ventures.